Muscle Atrophy Due to Nerve Damage Is Accompanied by Elevated Myofibrillar Protein Synthesis Rates - Langer, Henning T.; Senden, Joan M. G.; Gijsen, Annemie P.; Kempa, Stefan; van Loon, Luc J. C.; Spuler, Simone (Frontiers in Physiology, 2018)
Muscle loss is a severe complication of many medical conditions such as cancer, cardiac failure, muscular dystrophies and nerve damage. The contribution of myofibrillar protein synthesis (MPS) to the loss of muscle mass after nerve damage is not clear. Using deuterium oxide (D2O) labeling, we demonstrate that MPS is significantly increased in rat m. tibialis anterior (TA) compared to control (3.23±0.72 [damaged] to 2.09±0.26 %*day-1 [control]) after four weeks of nerve constriction injury. This is the case despite substantial loss of mass of the TA (350±96 mg [damaged] to 946±361 mg [control]). We also show that expression of regulatory proteins involved with MPS (p70s6k1: 2.4±0.3 AU [damaged] to 1.8±0.2 AU [control]) and muscle protein breakdown (MPB) (MAFbx: 5.3±1.2 AU [damaged] to 1.4±0.4 AU [control]) are increased in nerve damaged muscle. Furthermore, the expression of p70s6k1 correlates with MPS rates (r²=0.57). In conclusion, this study shows that severe muscle wasting following nerve damage is accompanied by increased as opposed to decreased myofibrillar protein synthesis.